IMPLEMENTASI PROGRAM PEMBANGUNAN DAN PEMBERDAYAAN MASYARAKAT (PROBEBAYA) DI KELURAHAN RAPAK DALAM TAHUN 2024 - Fikar Agung Muliya Sitepu; lutfi wahyudi (Jurnal Ilmu Pemerintahan, 2025)
Government Science Study Program, Faculty of Social and Political Sciences, Mulawarman University, Study of the Implementation of the Community Development and Empowerment Program in Rapak Dalam Subdistrict in 2024, under the guidance of Mr. Lutfi Wahyudi, S.Sos, M.Si. This study aims to explain the implementation of the Community Development and Empowerment Program (Probebaya) in Rapak Dalam Subdistrict in 2024. This research uses the theory of Policy Implementation by Van Metter and Van Horn by prioritizing the analysis of six important indicators, namely policy standards and objectives, resources, characteristics of implementing organizations, attitudes of implementers, communication between related organizations, and the social, economic and political environment. These six indicators are used to analyze the implementation of Probebaya in 29 RTs in Rapak Dalam Subdistrict in 2024. Furthermore, the author focuses on the development sector as one type of program that focuses on infrastructure development. The type of research used is qualitative using a descriptive approach. The results show that the implementation of the Community Development and Empowerment Program in Rapak Dalam Subdistrict in 2024 has not been realized as well as possible because there are nine out of 29 RTs that have not implemented Probebaya optimally. This happens because there are several obstacles in the implementation of several important indicators in the program, such as minimal resources, less participatory organizational characters, less contributive attitudes of implementers, and the social and economic environment that is still an obstacle.